Strategies to Cope With Students’ Discipline Problems in Senior High School - Aryati Prasetyarini; Mauly Halwat Hikmat; Mohammad Thoyibi (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
The article deals with the strategies implemented by teachers in facilitating the students to comply with the rules. The study aims at identifying the discipline problems faced by teachers and describing the strategies they employ to cope with the discipline problems. The study employed qualitative approach in which the researchers used questionnaire and interview to collect the data. The participants were high school teachers and students of 10 schools in Central Java, Indonesia from various backgrounds: public, private, Islam-based public, Islam-affiliated private, Islam-based dormitory. The interview script became the primary source for interpreting and analyzing data. The findings revealed that the most common discipline problems faced by the teachers were noisy classroom, wrong/incomplete attributes and unpunctuality. The strategies applied by the teachers to cope with the students were corrective, assertive, and preventive disciplines. The teachers should improve the quality in maintaining the classroom discipline by creating a conducive classroom and involving the students in setting the classroom rules, such as attendance, learning participation, students and teacher actions, and assessment.